(untitled) (Journal of Educational Sciences, 2017)
The article discusses the role and contribution of academicial T. Tazhibaev in the formation and development of pedagogy and psychology in Kazakhstan. The authors believe that the scientific works of the scientist, which reviewed and considered the philosophical, psychological and pedagogical views of Abay, Ibyray Altynsarin, Shokan Ualikhanov are a vivid legacy in domestic science. The article focuses on the educational importance, the importance of national heritage and ethnic aspects of ethnic pedagogical thoughts of the scientist. Systematic data about authors who have researched the scientific heritage of academician T. Tazhibaev. Pedagogical ideas of the scientist, the authors consider in continuity with the ideas of “Mangilik El”. The authors reveal the importance of the scientist in upbringing the younger generation and suggest the use of pedagogical and psychological legacy of T. Tazhibaevs in the embodiment of the idea “Mangilik El”.